Respon Ketahanan Beberapa Varietas Gandum terhadap Hama Gudang Sitophilus zeamais (Coleoptera: Dryophthoridae) - Lina Herlina; Bonjok Istiaji (Buletin Plasma Nutfah, 2013)
Resistance Response of Several Wheat Varieties Against Pest of Stored Product, Sitophilus zeamais (Coleoptera: Dryophthoridae). Lina Herlina and Bonjok Istiaji. Since Sitophilus zeamais still become the major pest of wheat as stored product. Twelve varieties of wheat were evaluated for their resistance to the infestation of S. zeamais. The study was conducted at the Laboratory of Insect Specimen Collection of Indonesian Center for Agriculture Biotechnology and Genetic Resource Research and Development (ICABIOGRAD) from September 2011 to February 2012. Grains of each 12 varieties of wheat was weighed for 5 grams and placed into a plastic bottle. Six female imagos of S. zeamais (1 week old) were introduced into the bottle contained 5 grams of wheat grains. After seven days, all the insects were removed. Observation were done to count the dead and life insects after introduction. The number of larvae emerged from eggs were calculated and weighed daily. Grain weight of each variety was also weighed, the broken and intact seeds were counted and recorded at the end of the infestation. Research were conducted in randomly complete design using one factor, that was twelve varieties of wheat each were replicated three times. The result showed that the highest mortality of the pest were in Perdix, while the lowest were that in Anemos, Combi, and Nandu (0-16.7%). The highest fertility of the pests were found in the Anemos and SW Triso, while the lowest were there in Picallo (14.33-47.67 insects). Anemos was known to be variety with the highest insects population weight, while the Picallo was the variety that inhibited insect population (0.0161-0.0544 g). The longest of insect development periods was on Combi, the shortest was on Sweta (51.33-64.33 days). The shortest median development time was in the Anemos and the longest was in the Sit Nortrend (37.33-44 days). The highest percentage of seed damage and yield loss were in the Anemos, while the lowest were Picallo and Madonna. ANOVA at 5% showed no significant different for all parameters observed on the tested varieties. Resistance classification based on the indexes of Modification, Pointe and Dobie recorded that the most resistant varieties were Picallo and Pasadena. AbstrakSitophilus zeamais masih menjadi hama utama pada produk pascapanen. Penelitian dilakukan di Laboratorium Koleksi Spesimen Serangga BB Biogen dari September 2011 sampai Februari 2012 untuk mengevaluasi ketahanan 12 varietas gandum terhadap infestasi S. zeamais. Biji 12 varietas masingmasing ditimbang 5 g dan dimasukkan ke dalam botol plastik, kemudian diintroduksikan enam imago betina S. zeamais berumur seminggu. Setelah tujuh hari, seluruh serangga dikeluarkan, dihitung yang mati dan yang masih hidup. Jumlah larva (progeni F1) yang muncul dari telur diamati dan dihitung setiap hari. Berat gandum tiap varietas ditimbang pada akhir percobaan. Biji yang berlubang maupun yang masih utuh dihitung dan dicatat. Penelitian menggunakan rancangan acak lengkap satu faktor, yaitu jenis varietas gandum sebanyak 12 varietas, masing-masing dengan tiga ulangan. Hasil percobaan menunjukkan bahwa mortalitas larva tertinggi ditemukan pada varietas Perdix, sedangkan terendah pada Anemos, Combi, dan Nandu (kisaran 0-16,7%). Fertilitas tertinggi ditemukan pada Anemos dan SW Triso, sedangkan terendah pada Picallo (kisaran 14,33-47,67 ekor). Bobot tertinggi larva serangga ditemukan pada Anemos, terendah pada Picallo (kisaran 0,0161- 0,0544 g). Perkembangan serangga terlama ditemukan pada Combi dan terpendek pada varietas Sweta (kisaran 51,33-64,33 hari). Waktu paruh terpendek pada varietas Anemos dan terpanjang pada varietas Sit Nortrend (kisaran 37,33-44 hari). Kerusakan biji maupun kehilangan hasil tertinggi pada varietas Anemos, sedangkan terendah pada Picallo dan Madonna. Hasil ANOVA pada taraf 5% menunjukkan tidak terdapat perbedaan pengaruh yang signifikan dari seluruh varietas terhadap semua parameter yang diamati. Berdasarkan indeks Modif, Pointe maupun Dobie, varietas yang paling tahan adalah Picallo dan Pasadena.